Comfort and Safety as Perceived by Wheelchair-Seated Bus Passengers - Wretstrand, Anders ; 0000-0002-7394-4534 (Transportation Planning and Technology, 2007)
Wheelchair-seated passengers on European and Swedish urban transit buses can travel rearwards, resting against a bulkhead, without the use of tiedown equipment. However, users sometimes disapprove of being the only passengers who have to travel rearwards, and also unrestrained. In order to investigate comfort and safety as perceived by wheelchair-seated bus passengers riding either forwards or rearwards, an experimental field study was carried out. Participating subjects were 31 wheelchair users and a group of 44 ambulant passengers. Each subject made two consecutive, identical 15-minute trips, randomly beginning either forwards or backwards, and interviews were conducted after each trip. During the trips, three-axis bus motion was recorded. The concept of categorization was used as a theoretical background and basis for discussion of the comfort and safety constructs. The results indicated that while the majority preferred the forward-facing position regarding comfort issues, a minority felt that the level of perceived safety was better. Wheelchair-seated passengers were more positive towards the rearward position than the ambulant group.
Keywords: Wheelchair-seated passenger; comfort; bus; safety